Poland Structural Policies for Competitiveness : Position Paper for Regulatory Policy - World Bank Group (World Bank, Washington, DC, 2018)
Regulatory policy is essential for economic growth and social welfare. Regulations are the rules set by the state to govern the daily life of citizens and businesses. Regulatory policy, the prerogative to establish these rules, is a key lever of state power. Poland has made progress in improving the quality of its regulatory processes, but important challenges remain. High quality regulations are essential for a sound legal framework based on certitude, legality, and transparency. The strategy for responsible development (SRD) recognizes the importance of regulation to stimulate economic activity in Poland. As the main policy document for economic transformation, the SRD identifies shortcomings in the current development model and makes proposals on how to address them. The strategy offers a good starting point to identify areas in which the World Bank could engage with the Government of Poland to further support the efforts to strengthen a sound regulatory environment for business. This position paper aims at: (i) assessing some of the current efforts made by the Government of Poland in terms of regulatory policy, particularly affecting business; and (ii) identifying areas of potential engagement between the World Bank and the Government of Poland.